ЕПІФІТНА МІКРОФЛОРА РОСЛИН РИСУ (ORYZA SATIVA L.) ЯК ДЖЕРЕЛО ШТАМІВ З АГРОНОМІЧНО КОРИСНИМИ ДЛЯ РОСЛИН ВЛАСТИВОСТЯМИ - Якубовська, А. І. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2014)
The paper covers the study of morphological, physiological and biochemical properties of associative microorganisms isolated from rice roots and plants’ response on inoculation. The agronomically useful properties, such as growth stimulation, ability to fix nitrogen and mobilize phosphates were observed. The positive influence of isolated bacteria on growth and development of rice plants was observed.